Serum Interleukin 23 in Psoriatic Arthritis Patients: Relation to disease activity, physical function and health related quality of life - Elsawy, Noha Abdelhalim; Helal, Abdelmoniem; El Shafei, Mohamed; Mikhael, Neveen Lewis; Aboeladl, Nesrin Ahmed (Aktuelle Rheumatologie, 2019)
Objective To assess interleukin 23 (IL-23) levels in the sera of psoriatic arthritis (PsA) patients and to determine the relationship of IL-23 with different disease activity indices, physical function and quality of life (QoL).Methods Fifty PsA patients and 46 matched healthy controls were included in this study. Data including a detailed history, a thorough clinical examination, skin severity based on the Psoriasis Area and Severity Index (PASI), the Disease Activity index for Psoriatic Arthritis (DAPSA) and the Composite Psoriatic Disease Activity Index (CPDAI) were obtained for all patients. Physical function was assessed by the Health Assessment Questionnaire Disability Index (HAQ-DI) and health-related QoL was assessed using the Short Form Health Survey (SF-36), Psoriatic Arthritis Quality of Life (PsAQoL) and the Dermatology Life Quality Index (DLQI) were also assessed. Serum IL-23 levels were measured in the studied groups.Results The study included 23(46%) females and 27 (54%) males with a mean age of 42.78±12.33 years. The mean serum IL-23 level was significantly higher in PsA patients (50.89±13.86 pg/ml) than in controls (43.88±6.34 pg/ml) (p=0.006). There were significant correlations between serum IL-23 levels and different grades of DAPSA activity (p=0.007) and PASI (p=0.015). No significant correlations could be detected between serum IL-23 levels and (HAQ-DI, DLQI, SF-36 or PsAQoL). CPDAI and DAPSA were significantly correlated with DLQI, SF-36 and PsAQoL.Conclusion IL-23 is a useful biomarker for identifying joint activity or skin severity but not QoL or physical function.
Keywords: PsA; IL-23; DAPSA; SF-36; PsAQoL